Automorphisms of finite cyclic 3-groups - Fatin Hanani, Hasan; Mohd Sham, Mohamad; Yuhani, Yusof (American Institute of Physics, 2024)
A distinct compatible pair of actions will result in distinct nonabelian tensor products. This proves that the number of compatible pairs of action plays a huge role as the greatest variety nonabelian tensor product relies on it. However, the actions of finite cyclic group are defined by automorphisms, thus the number of automorphisms needs to be known before obtaining the number of actions that are compatible with one another. This paper focuses on determining the automorphism finite cyclic 3-groups. The general presentation of the automorphism of such groups is obtained with the help of Groups, Algorithm, and Programming (GAP) Software.